Michael S. Hogue, American Immanence: Democracy for an Uncertain World - Wheeler, Demian (Journal for the Study of Religion, Nature and Culture, 2021)
Michael S. Hogue, American Immanence: Democracy for an Uncertain World (New York: Columbia University Press, 2018), 256 pp., 30.00 (pbk), ISBN: 9780231172332.